2012
DOI: 10.1242/jeb.064980
|View full text |Cite
|
Sign up to set email alerts
|

Aging modulates cuticular hydrocarbons and sexual attractiveness inDrosophila melanogaster

Abstract: SUMMARY Attractiveness is a major component of sexual selection that is dependent on sexual characteristics, such as pheromone production, which often reflect an individual’s fitness and reproductive potential. Aging is a process that results in a steady decline in survival and reproductive output, yet little is known about its effect on specific aspects of attractiveness. In this report we asked how aging impacts pheromone production and sexual attractiveness in Drosophila melanogaster. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 44 publications
6
93
0
Order By: Relevance
“…A change in the CHC profiles during ageing and a decreasing sexual attractiveness was recently also reported in Drosophila melanogaster (Kuo et al, 2012). As previously shown in our studies on L. distinguendus (Steiner et al, 2005;Steiner et al, 2007), the authors found a shift towards compounds with longer chain-lengths and observed a correlation with decreasing sexual attractiveness.…”
Section: Discussionsupporting
confidence: 89%
“…A change in the CHC profiles during ageing and a decreasing sexual attractiveness was recently also reported in Drosophila melanogaster (Kuo et al, 2012). As previously shown in our studies on L. distinguendus (Steiner et al, 2005;Steiner et al, 2007), the authors found a shift towards compounds with longer chain-lengths and observed a correlation with decreasing sexual attractiveness.…”
Section: Discussionsupporting
confidence: 89%
“…45 For example, CHC profiles changed in consistent ways most notably by producing higher proportions of long-chain compounds with increasing age in females from 2 different fly strains. 39 A young female CHC profile was both necessary and sufficient for males to discriminate between chronologically young and old females; male courtship preferences for young vs. old females corresponded with the female CHC profiles, disappeared when CHCs were removed from young and old females by hexane washing, and could be re-directed toward older females when coated in CHCs from younger females (8 d pe vs 52 d pe; 39 ). Female receptivity peaks at >90% 1-2 d pe, then begins to decline approximately 7 d pe in virgin females 27,35,37 and as early as 5 d pe in previously-mated females.…”
Section: Courtship and Matingmentioning
confidence: 98%
“…38 While male courtship vigor toward active (intact) females has not been observed to change with increasing female age (5 d-20 d post-eclosion, hereafter abbreviated as d pe; 37 ), male discrimination based on female age is detected under conditions where some female stimuli are isolated. When females are immobilized and decapitated to prevent rejection responses, males spend »50% less time courting old females than young females (female ages 20 d-1 d pe, 36 ; 52 d vs 8 d pe, 39 ). However, female movement is an important visual signal for mate recognition and courtship initiation.…”
Section: Courtship and Matingmentioning
confidence: 99%
“…An age-dependent response to a sexual pheromone is common in many arthropods (e.g. Klein et al 2012) and can be caused by a variety of factors like age-related variation in the pheromone emission and composition (Coppee et al 2011;Kuo et al 2012;Wang et al 2015) or hormone-triggered behavioural plasticity (Duportets et al 2013;Jarriault et al 2009). Mating of A. tumida follows a fixed order of behaviours which is often interrupted by aggressive females.…”
Section: Discussionmentioning
confidence: 99%